Polyimide Resin
Patent Information
- Application Number
- JP2020157512
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-15
- Filing Date
- 2020-09-18
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-09-18
AI Technical Summary
【0008】 本発明のポリイミド系樹脂は、高破断歪と低熱膨張係数とを両立可能な光学フィルムを形成できる。そのため、本発明のポリイミド系樹脂は、フレキシブル表示装置の材料等に好適に使用できる。
Smart Images

Figure 0007645060000001 
Figure 0007645060000002 
Figure 0007645060000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide resin used as a material for flexible display devices, an optical film containing the polyimide resin, and a flexible display device including the optical film. [Background technology]
[0002] Display devices such as liquid crystal display devices and organic electroluminescence display devices are widely used for various applications such as mobile phones and smart watches. Glass has been used as the front panel of such display devices, but glass is very rigid and easily broken, making it difficult to use as the front panel material for flexible display devices. Optical films using polymers such as polyimide resins are being considered as an alternative material to glass. Patent Document 1 discloses a polyimide resin containing 70 mol % or more of a structural unit derived from an ester-type tetracarboxylic dianhydride formed by esterifying a biphenyl-4,4'-diol with two trimellitic acids, and a polyimide film formed from the polyimide resin. The polyimide film formed from such a polyimide resin is advantageous in that it has heat resistance and a low thermal expansion coefficient. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2014 / 046180 Summary of the Invention [Problem to be solved by the invention]
[0004] Polyimide films used as materials for flexible display devices are required to have a low thermal expansion coefficient as well as a high breaking strain. However, according to the study by the present inventors, it was found that a film made of a polyimide resin such as that disclosed in Patent Document 1 has a low thermal expansion coefficient but a low breaking strain, and therefore it is not possible to achieve both a high breaking strain and a low thermal expansion coefficient.
[0005] Therefore, an object of the present invention is to provide a polyimide-based resin capable of forming an optical film that can achieve both a high breaking strain and a low thermal expansion coefficient, the optical film, and a flexible display device including the optical film. [Means for solving the problem]
[0006] As a result of intensive research to solve the above problems, the present inventors have found that the above problems can be solved when Y in formula (1) contains a structure represented by formula (3) and a structure represented by formula (5), and the proportion of Y represented by formula (5) among the structural units represented by formula (1) exceeds 30 mol%, and have completed the present invention. That is, the present invention includes the following preferred embodiments.
[0007] [1] Formula (1): [ka] [In formula (1), X represents a divalent organic group, Y represents a tetravalent organic group; * represents a bond. The compound represented by the formula (3): [ka] [In formula (3), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; R 2 ~R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; m each independently represents an integer of 0 to 3; n represents an integer of 1 to 4; * represents a bond, except for R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 at least three of which are monovalent hydrocarbon groups which may have a halogen atom. and a structure represented by formula (5): [ka] [In formula (5), B is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; t's each independently represent an integer of 0 to 3; * represents a bond. and, among the constitutional units represented by formula (1), the proportion of constitutional units in which Y is represented by formula (5) exceeds 30 mol %. [2] The polyimide resin according to [1], wherein X in the formula (1) contains at least one of a divalent aromatic group, a divalent alicyclic group, and a divalent aliphatic group. [3] In formula (1), X is represented by formula (4): [ka] [In formula (4), A is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R A1 )- or -Si(R A2)2-, R A1 and R A2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 6 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; Each s independently represents an integer of 0 to 4; * represents a bond. The polyimide resin according to [1] or [2], which contains a structure represented by the following formula: [4] The polyimide resin according to any one of [1] to [3], which has a weight-average molecular weight of 160,000 or more. [5] An optical film comprising the polyimide resin according to any one of [1] to [4]. [6] The optical film according to [5], having a total light transmittance of 85% or more. [7] The optical film according to [5] or [6], which has a yellowness index of 3.0 or less. [8] The optical film according to any one of [5] to [7], which has an elastic modulus of 3.5 GPa or more. [9] The optical film according to any one of [5] to [8], which is a film for use as a front panel of a flexible display device.
[10] A flexible display device comprising the optical film according to any one of [5] to [9].
[11] The flexible display device according to
[10] , further comprising a touch sensor.
[12] The flexible display device according to
[10] or
[11] , further comprising a polarizing plate. Effect of the Invention
[0008] The polyimide resin of the present invention can be used to form an optical film that can achieve both a high breaking strain and a low thermal expansion coefficient, and therefore can be suitably used as a material for flexible display devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Polyimide resin] The polyimide resin of the present invention has the formula (1): [ka] [In formula (1), X represents a divalent organic group, Y represents a tetravalent organic group; * represents a bond. It contains a structural unit represented by:
[0010] In formula (1), Y's each independently represent a tetravalent organic group, preferably a tetravalent organic group having 4 to 80 carbon atoms, more preferably a tetravalent organic group having 4 to 60 carbon atoms and having a cyclic structure. Examples of the cyclic structure include an alicyclic ring, an aromatic ring, and a heterocyclic structure. The organic group is an organic group in which a hydrogen atom in the organic group may be substituted with a substituent, and the substituent is preferably a halogen atom, a monovalent hydrocarbon group that may have a halogen atom, such as an alkyl group, an aryl group, an alkoxy group, or an aryloxy group, and in such a case, the number of carbon atoms in the monovalent hydrocarbon group, alkoxy group, or aryloxy group that may have a halogen atom is preferably 1 to 8. The polyimide resin according to one embodiment of the present invention may contain multiple types of Y, and the multiple types of Y may be the same or different from each other.
[0011] In the polyimide resin of the present invention, Y in formula (1) is represented by formula (3): [ka] [In formula (3), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; R 2 ~R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; m each independently represents an integer of 0 to 3; n represents an integer of 1 to 4; * represents a bond, except for R 2 ~R 5In at least one benzene ring having R 2 ~R 5 at least three of which are monovalent hydrocarbon groups which may have a halogen atom. and a structure represented by formula (5): [ka] [In formula (5), B is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; t's each independently represent an integer of 0 to 3; * represents a bond. and the proportion of constitutional units in which Y is represented by formula (5) exceeds 30 mol % among constitutional units represented by formula (1).
[0012] The present inventors have found that by adjusting the proportion of the structural unit represented by formula (5) in formula (1) to more than 30 mol %, the breaking strain of the obtained optical film can be improved, and even if the proportion of the structural unit exceeds 30 mol %, R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 It has been found that if at least three of the units are monovalent hydrocarbon groups which may have a halogen atom, the thermal expansion coefficient of the obtained optical film can be kept low. Since the polyimide resin of the present invention has such structural units, it is possible to form an optical film which can achieve both a high breaking strain and a low thermal expansion coefficient, which have been difficult to achieve in the past.
[0013] In formula (3), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. Examples of halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. Examples of alkyl groups include methyl groups, ethyl groups, n-propyl groups, isopropyl groups, n-butyl groups, isobutyl groups, sec-butyl groups, tert-butyl groups, n-pentyl groups, 2-methyl-butyl groups, 3-methylbutyl groups, 2-ethyl-propyl groups, and n-hexyl groups. Examples of alkoxy groups include methoxy groups, ethoxy groups, propyloxy groups, isopropyloxy groups, n-butoxy groups, isobutoxy groups, sec-butoxy groups, tert-butoxy groups, pentyloxy groups, hexyloxy groups, and cyclohexyloxy groups. Examples of aryl groups include phenyl groups, tolyl groups, xylyl groups, naphthyl groups, and biphenyl groups. Examples of the aryloxy group include a phenoxy group, a naphthyloxy group, and a biphenyloxy group. 1 each independently represents preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aryloxy group having 6 to 12 carbon atoms. From the viewpoint of easily improving the elastic modulus and transparency of an optical film containing a polyimide resin (hereinafter, sometimes simply referred to as an optical film) and easily reducing the thermal expansion coefficient, R 1 are preferably, independently of each other, an alkyl group or an alkoxy group which may have a halogen atom, and more preferably an alkyl group having 1 to 6 carbon atoms or an alkoxy group having 1 to 6 carbon atoms which may have a halogen atom.
[0014] In formula (3), from the viewpoint of easily improving the elastic modulus and transparency of the optical film and easily reducing the thermal expansion coefficient, m's each independently represent an integer of 0 to 3, preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0015] In formula (3), R 2 , R 3, R 4 and R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; R 2 ~R 5 In at least one benzene ring having R 2 ~R 5 At least three of the above are monovalent hydrocarbon groups which may have halogen atoms. Examples of the hydrocarbon group include aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and aliphatic hydrocarbon groups. Examples of the aromatic hydrocarbon group include aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl. Examples of the alicyclic hydrocarbon group include cycloalkyl groups such as cyclopentyl and cyclohexyl. Examples of the aliphatic hydrocarbon group include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 2-methylbutyl, 3-methylbutyl, 2-ethylpropyl, n-hexyl, n-heptyl, n-octyl, tert-octyl, n-nonyl, and n-decyl. Examples of the halogen atom include those described above. R 2 ~R 5 each independently represents preferably a hydrogen atom, or an aryl group having 6 to 12 carbon atoms, a cycloalkyl group having 4 to 8 carbon atoms, or an alkyl group having 1 to 6 carbon atoms, which may have a halogen atom. From the viewpoint of easily improving the solubility of the resin in a solvent, and the elastic modulus and transparency of the optical film, and easily reducing the thermal expansion coefficient, R 2 ~R 5 are each independently preferably a hydrogen atom or an alkyl group which may have a halogen atom, more preferably a hydrogen atom or an alkyl group having 1 to 6 carbons which may have a halogen atom, and further preferably a hydrogen atom or an alkyl group having 1 to 3 carbons which may have a halogen atom.
[0016] R in Equation (3) 2 ~R 5 In at least one benzene ring having R 2 ~R 5In the present invention, when the number of monovalent hydrocarbon groups which may have halogen atoms is less than three, particularly when the proportion of the structural unit represented by formula (5) in which Y is more than 30 mol %, the thermal expansion coefficient is likely to increase, making it difficult to achieve both a low thermal expansion coefficient and a high breaking strain. 2 ~R 5 In at least one benzene ring having R 2 ~R 5 At least three of the groups are monovalent hydrocarbon groups which may have a halogen atom, so that the breaking strain can be improved while maintaining a low thermal expansion coefficient, and the solubility of the resin in a solvent can also be improved.
[0017] From the viewpoint of making it easier to improve the solubility of the resin in a solvent, and the breaking strain, elastic modulus, and transparency of the optical film, and to make it easier to reduce the thermal expansion coefficient, when n is 2 or more, R 2 ~R 5 In at least two benzene rings having R 2 ~R 5 It is more preferable that at least three of R are monovalent hydrocarbon groups which may have a halogen atom. 2 ~R 5 In all benzene rings having R 2 ~R 5 It is more preferable that at least three of the above be monovalent hydrocarbon groups which may have a halogen atom.
[0018] In formula (3), n represents an integer of 1 to 4, and from the viewpoint of easily improving the elastic modulus and transparency of the optical film and easily reducing the thermal expansion coefficient, n is preferably an integer of 1 to 3, more preferably 2 or 3, and further preferably 2. The constitutional unit represented by formula (1) may contain one or more types of structures represented by formula (3) as Y.
[0019] In a preferred embodiment of the present invention, formula (3) is represented by formula (3'): [ka] [In formula (3'), * represents a bond] That is, at least a part of the multiple Ys in formula (1) is represented by formula (3'). In this form, it is easy to improve the elastic modulus and transparency of the optical film, and it is easy to reduce the thermal expansion coefficient.
[0020] In one embodiment of the present invention, the ratio of the structural units represented by formula (1) in which Y is represented by formula (3) is preferably 10 mol% or more, more preferably 30 mol% or more, even more preferably 45 mol% or more, even more preferably 50 mol% or more, particularly preferably 55 mol% or more, and preferably less than 70 mol%, more preferably 65 mol% or less, even more preferably 62 mol% or less, particularly preferably 60 mol% or less, relative to the total molar amount of the structural units represented by formula (1). When the ratio of the structural units represented by formula (3) in which Y is represented by formula (3) is equal to or more than the above lower limit, the elastic modulus of the optical film is easily increased and the thermal expansion coefficient is easily reduced. When the ratio of the structural units represented by formula (3) in which Y is represented by formula (3) is equal to or less than the above upper limit, the breaking strain and transparency of the optical film are easily increased. The ratio of the structural units represented by formula (3) in which Y is represented by formula (3) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0021] In the polyimide resin of the present invention, Y in formula (1) may further be represented by formula (5): [ka] [In formula (5), B is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; t's each independently represent an integer of 0 to 3; * represents a bond. When Y in formula (1) contains a structure represented by formula (5), the breaking strain, elastic modulus, and transparency of the optical film are easily improved.
[0022] In formula (5), R 7 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The halogen atom, the alkyl group, the alkoxy group, the aryl group, and the aryloxy group which may have a halogen atom are each represented by R 1 From the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film, R 7 are each independently preferably an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, and more preferably an alkyl group having 1 to 3 carbon atoms which may have a halogen atom.
[0023] In formula (5), t represents an integer of 0 to 3, and from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film, it preferably represents an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0024] In the formula (5), each B is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -COO-, -PO-, -PO2-, -N(R B1 )- or -Si(R B2 )2-, R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom.
[0025] The divalent hydrocarbon group which may have a halogen atom is R 2 ~R 5Among the monovalent hydrocarbon groups which may have a halogen atom in the above formula, a divalent group in which one hydrogen atom has been further removed can be mentioned. The divalent hydrocarbon group which may have a halogen atom can form a ring by replacing two of the hydrogen atoms contained in the group, that is, the two hydrogen atoms can be replaced with bonds and the two bonds can be linked to form a ring. Examples of such rings include a cycloalkane ring having 3 to 12 carbon atoms. In addition, -N(R B1 )- and -Si(R B2 )2-R B1 and R B2 The alkyl group which may have a halogen atom in the formula (3) is R 1 Examples of the alkyl group which may have a halogen atom include those exemplified above.
[0026] From the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film, B in formula (5) is preferably a single bond or a divalent hydrocarbon group which may have a halogen atom, more preferably a single bond, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2- or -C(CF3)2-, even more preferably a single bond, -C(CH3)2- or -C(CF3)2-, still more preferably a single bond or -C(CF3)2-, and particularly preferably -C(CF3)2-.
[0027] In a preferred embodiment of the present invention, formula (5) is represented by formula (5'): [ka] [In formula (5'), * represents a bond] That is, at least a part of the multiple Ys in formula (1) is represented by formula (5'). With such a form, it is easy to improve the breaking strain, elastic modulus, and transparency of the optical film.
[0028] Among the structural units represented by formula (1), the proportion of structural units in which Y in formula (1) is represented by formula (5) exceeds 30 mol% relative to the total molar amount of structural units represented by formula (1). When the proportion of structural units in which Y in formula (1) is represented by formula (5) is 30 mol% or less, the breaking strain of the optical film tends to decrease. In the present invention, since the proportion of structural units in which Y is represented by formula (5) exceeds 30 mol%, the obtained optical film can have an excellent breaking strain. The proportion of the structural unit represented by Y in formula (1) represented by formula (5) is preferably 35 mol% or more, more preferably 38 mol% or more, and even more preferably 40 mol% or more, relative to the total molar amount of the structural unit represented by formula (1), and is preferably 90 mol% or less, more preferably 70 mol% or less, even more preferably 55 mol% or less, even more preferably 50 mol% or less, and particularly preferably 45 mol% or less. When the proportion of the structural unit represented by Y in formula (5) is equal to or more than the above lower limit, the breaking strain and transparency of the optical film are easily increased. When the proportion is equal to or less than the above upper limit, the elastic modulus of the optical film is easily increased and the thermal expansion coefficient is easily reduced. The proportion of the structural unit represented by Y in formula (5) in formula (1) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0029] The ratio of the structural unit in which Y in formula (1) is represented by formula (3) is preferably 0.1 mol or more, more preferably 0.4 mol or more, and even more preferably 1.0 mol or more, and is preferably 2.3 mol or less, more preferably 1.9 mol or less, and even more preferably 1.7 mol or less, relative to 1 mol of the structural unit in which Y in formula (1) is represented by formula (5). When the ratio of the structural unit in which Y in formula (1) is represented by formula (3) relative to the structural unit in which Y in formula (1) is represented by formula (5) is equal to or more than the above lower limit, the elastic modulus of the optical film is easily increased and the thermal expansion coefficient is easily reduced. When the ratio is equal to or less than the above upper limit, the breaking strain and transparency of the optical film are easily increased. The ratio of the structural unit in which Y in formula (1) is represented by formula (3) relative to the structural unit in which Y in formula (1) is represented by formula (5) is, for example, 1It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0030] In formula (1), Y can be any of the structures represented by formula (3) and (5), as well as the structures represented by formula (20), (21), (22), (23), (24), (25), (26), (27), (28) and (29):
[0031] [ka] The compound may include a structure represented by the following formula:
[0032] In formulas (20) to (29), * represents a bond, W 1 represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, for example, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, etc., -Ar-, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R W1 )-, -Si(R W2 R represents -O-Ar-O-, -Ar-O-Ar-, -Ar-CH2-Ar-, -Ar-C(CH3)2-Ar-, or -Ar-SO2-Ar-. Ar represents an arylene group having 6 to 20 carbon atoms which may have a fluorine atom, and a specific example thereof is a phenylene group. W1 and R W2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom. The hydrogen atom in the group represented by formula (20) to formula (29) may be a group substituted with a methyl group, a fluoro group, a chloro group, or a trifluoromethyl group; or a tetravalent chain hydrocarbon group having 6 or less carbon atoms. The hydrogen atom on the ring in formula (20) to formula (29) may be substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms are each represented by R in formula (3). 1 Examples of such a substance include those exemplified above.
[0033] Among the groups represented by formulae (20) to (29), from the viewpoints of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, the groups represented by formula (26), formula (28), and formula (29) are preferred, and the group represented by formula (26) is more preferred. 1 From the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, preferably represents a single bond, -O-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, or -C(CF3)2-, more preferably a single bond, -O-, -CH2-, -CH(CH3)-, -C(CH3)2-, or -C(CF3)2-, even more preferably a single bond, -C(CH3)2-, or -C(CF3)2-, still more preferably a single bond or -C(CF3)2-, and particularly preferably -C(CF3)2-.
[0034] In one embodiment of the present invention, the total ratio of the structural unit in which Y is represented by formula (3) and the structural unit in which Y is represented by formula (5) is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and preferably 100 mol% or less, based on the total molar amount of the structural unit represented by formula (1). When the total ratio is within the above range, the breaking strain, elastic modulus, and transparency of the optical film are easily improved, and the thermal expansion coefficient is easily reduced. The total ratio can be, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0035] In formula (1), X represents a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms.
[0036] From the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, the polyimide resin of the present invention preferably contains at least one of a divalent aromatic group, a divalent alicyclic group, and a divalent aliphatic group as X in formula (1), and more preferably contains a divalent aromatic group. 2 ~R5 a divalent aromatic hydrocarbon group in which one of the hydrogen atoms in the aromatic hydrocarbon group exemplified above is replaced by a bond; at least one of the divalent aromatic hydrocarbon groups is replaced by a linking group, for example, 1 Examples of the divalent alicyclic group include groups bonded via a linking group such as R 2 ~R 5 a divalent alicyclic hydrocarbon group in which one of the hydrogen atoms in the alicyclic hydrocarbon group exemplified above is replaced by a bond; 1 Examples of the divalent aliphatic group include groups bonded via a linking group such as R 2 ~R 5 a divalent aliphatic hydrocarbon group in which one of the hydrogen atoms in the aliphatic hydrocarbon group exemplified above is replaced by a bond; at least one of the divalent aliphatic hydrocarbon groups is replaced by a linking group, for example, 1 Examples of such groups include groups bonded via a linking group such as the above.
[0037] X in formula (1) preferably represents a divalent organic group having 4 to 40 carbon atoms and a cyclic structure such as an alicyclic ring, an aromatic ring, or a heterocyclic structure, more preferably a divalent aromatic group having 4 to 40 carbon atoms and a divalent alicyclic group having 4 to 40 carbon atoms, and further preferably a divalent aromatic group having 4 to 40 carbon atoms. The organic group may have a hydrogen atom substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group, and in that case, the number of carbon atoms in the hydrocarbon group and the fluorine-substituted hydrocarbon group is preferably 1 to 8. In one embodiment of the present invention, the polyimide resin of the present invention may contain multiple types of X, and the multiple types of X may be the same or different from each other. Examples of X include groups represented by formula (10), formula (11), formula (12), formula (13), formula (14), formula (15), formula (16), formula (17) and formula (18); groups in which hydrogen atoms in the groups represented by formulas (10) to (18) are substituted with methyl groups, fluoro groups, chloro groups or trifluoromethyl groups; and chain hydrocarbon groups having 6 or less carbon atoms.
[0038] [ka]
[0039] In formulas (10) to (18), * represents a bond, V 1 , V 2 and V 3 are each independently a single bond, -O-, -S-, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, -C(CF3)2-, -SO2-, -CO-, or -N(Q)-. Here, Q represents a monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom. Examples of the monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom include R in formula (3). 2 ~R 5 Examples of the monovalent hydrocarbon group which may have a halogen atom in the formula (I) include those exemplified above. One example is V 1 and V 3 is a single bond, -O- or -S-, and V 2 is -CH2-, -C(CH3)2-, -C(CF3)2- or -SO2-. 1 and V 2 The bonding positions of each ring and V 2 and V 3 The bonding positions of each of the rings are, independently of each other, preferably meta-position or para-position, more preferably para-position, relative to each ring. In addition, the hydrogen atoms on the rings in formulas (10) to (18) may be substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. The alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms are each preferably substituted with R in formula (3). 1 Examples of such a substance include those exemplified above.
[0040] In a preferred embodiment of the present invention, the polyimide resin of the present invention has a structure represented by the formula (4): [ka] [In formula (4), A is a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R A1 )- or -Si(R A2 )2-, R A1 and R A2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 6 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; Each s independently represents an integer of 0 to 4; * represents a bond. In this embodiment, the breaking strain, elastic modulus, and transparency of the optical film are easily improved, and the thermal expansion coefficient is easily reduced. In addition, the structural unit represented by formula (1) may contain one or more structures represented by formula (4) as X.
[0041] R 6 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom. The halogen atom, the alkyl group, the alkoxy group, the aryl group, and the aryloxy group which may have a halogen atom are each represented by R 1 Examples of such a substance include those exemplified above.
[0042] Among these, R 6 are each independently preferably an alkyl group having 1 to 6 carbon atoms or a halogenated alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms or a fluoroalkyl group having 1 to 6 carbon atoms, and preferably a perfluoroalkyl group, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient. 6are each independently a methyl group, a chloro group, or a trifluoromethyl group. s's are each independently an integer of 0 to 4, and from the viewpoints of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, are preferably an integer of 1 to 3, more preferably 1 or 2, and even more preferably 1. In a preferred embodiment of the present invention, in each benzene ring, s is 1, and R 6 is substituted and R 6 is preferably a methyl group, a fluoro group, a chloro group or a trifluoromethyl group.
[0043] In formula (4), the positions of the bonds are preferably meta or para, and more preferably para, based on -A-, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient.
[0044] In formula (4), each A is independently a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R A1 )- or -Si(R A2 )2-, R A1 and R A2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom. The divalent hydrocarbon group which may have a halogen atom is R in the formula (3). 2 ~R 5 Among the monovalent hydrocarbon groups which may have a halogen atom in the above formula, a divalent group in which one hydrogen atom has been further removed can be mentioned. The divalent hydrocarbon group which may have a halogen atom can form a ring by replacing two of the hydrogen atoms contained in the group, that is, the two hydrogen atoms can be replaced with bonds and the two bonds can be linked to form a ring, and examples of such rings include a cycloalkane ring having 3 to 12 carbon atoms. In addition, -N(R A1 )- and -Si(R A2 )2-R A1 and RA2 The alkyl group which may have a halogen atom in the formula (3) is R 1 Examples of the alkyl group which may have a halogen atom include those exemplified above.
[0045] In terms of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, A in formula (3) is preferably a single bond, -CH2-, -CH2-CH2-, -CH(CH3)-, -C(CH3)2-, or -C(CF3)2-, more preferably a single bond, -C(CH3)2-, or -C(CF3)2-, even more preferably a single bond or -C(CF3)2-, and particularly preferably a single bond.
[0046] In a preferred embodiment of the present invention, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, R 6 each independently represents a halogenated alkyl group having 1 to 6 carbon atoms, s is 1 or 2, and A represents a single bond, -C(CH3)2- or -C(CF3)2-.
[0047] In a preferred embodiment of the present invention, formula (4) is represented by formula (4'): [ka] That is, at least a part of the multiple Xs in formula (1) is represented by formula (4'). In this form, it is easy to improve the breaking strain, elastic modulus, and transparency of the optical film, and it is easy to reduce the thermal expansion coefficient. The constitutional unit represented by formula (1) may contain one or more types of structures represented by formula (4') as X.
[0048] In one embodiment of the present invention, when X in formula (1) contains a structure represented by formula (4), the proportion of the structural units represented by formula (4) in which X is the structural unit represented by formula (4) is preferably 30 mol% or more, more preferably 50 mol% or more, even more preferably 70 mol% or more, even more preferably 80 mol% or more, particularly preferably 90 mol% or more, and preferably 100 mol% or less, based on the total molar amount of the structural units represented by formula (1). When the proportion of the structural units represented by formula (4) in which X is the structural unit represented by formula (4) is within the above range, the breaking strain, elastic modulus, and transparency of the optical film are easily improved, and the thermal expansion coefficient is easily reduced. The proportion of the structural units represented by formula (4) in which X is the structural unit represented by formula (4) is, for example, 1 It can be measured using H-NMR, or can be calculated from the ratio of the raw materials used.
[0049] The polyimide resin of the present invention may contain, in addition to the constitutional unit represented by formula (1), a constitutional unit represented by formula (30) and / or a constitutional unit represented by formula (31). [ka]
[0050] In formula (30), Y 1 Y is a tetravalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 Examples of the Y include groups represented by formula (20), (21), (22), (23), (24), (25), (26), (27), (28) and (29), groups in which hydrogen atoms in the groups represented by formulas (20) to (29) are substituted with methyl groups, fluoro groups, chloro groups or trifluoromethyl groups, and tetravalent chain hydrocarbon groups having 6 or less carbon atoms. In one embodiment of the present invention, the polyimide resin contains a plurality of types of Y 1 and may include multiple types of Y 1 may be the same or different from each other.
[0051] In formula (31), Y 2Y is a trivalent organic group, preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 2 Examples of the Y include a group in which any one of the bonds of the groups represented by the above formulae (20), (21), (22), (23), (24), (25), (26), (27), (28), and (29) is replaced with a hydrogen atom, and a trivalent chain hydrocarbon group having 6 or less carbon atoms. In one embodiment of the present invention, the polyimide resin contains a plurality of types of Y 2 and may include multiple types of Y 2 may be the same or different from each other.
[0052] In formula (30) and formula (31), X 1 and X 2 are each independently a divalent organic group, and preferably an organic group in which a hydrogen atom may be substituted with a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 and X 2 Examples of such a group include the groups represented by the above formulae (10), (11), (12), (13), (14), (15), (16), (17) and (18); groups in which hydrogen atoms in the groups represented by the formulae (10) to (18) are substituted with methyl groups, fluoro groups, chloro groups or trifluoromethyl groups; and chain hydrocarbon groups having 6 or less carbon atoms.
[0053] In one embodiment of the present invention, the polyimide resin comprises a structural unit represented by formula (1), and optionally at least one structural unit selected from the structural unit represented by formula (30) and the structural unit represented by formula (31). From the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, the proportion of the structural unit represented by formula (1) in the polyimide resin is preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more, and usually 100 mol% or less, based on the total molar amount of all structural units contained in the polyimide resin, for example, the structural unit represented by formula (1), and optionally at least one structural unit selected from the structural unit represented by formula (30) and the structural unit represented by formula (31). The above proportion can be, for example, 1 The thermal expansion coefficient can be easily reduced and the thermal expansion coefficient can be easily increased.
[0054] The weight average molecular weight (hereinafter sometimes abbreviated as Mw) of the polyimide resin of the present invention is preferably 160,000 or more, more preferably 180,000 or more, even more preferably 200,000 or more, even more preferably 250,000 or more, particularly preferably 300,000 or more, particularly preferably 350,000 or more, and preferably 1,000,000 or less, more preferably 800,000 or less, even more preferably 700,000 or less, particularly preferably 600,000 or less. When the Mw of the polyimide resin is the above lower limit or more, the transparency, elastic modulus and breaking strain of the obtained optical film are easily improved, and when the Mw is the above upper limit or less, the gelation of the resin varnish is easily suppressed, and the optical properties of the obtained optical film are easily improved. Note that Mw can be determined, for example, by gel permeation chromatography (hereinafter sometimes referred to as GPC) measurement and standard polystyrene conversion, for example, by the method described in the Examples.
[0055] In a preferred embodiment of the present invention, the polyimide resin of the present invention may contain halogen atoms such as fluorine atoms, which can be introduced, for example, by the above-mentioned fluorine-containing substituents. When the polyimide resin contains halogen atoms, the yellowness index (hereinafter sometimes referred to as YI value) of the optical film is easily reduced, and the breaking strain and elastic modulus are easily increased. In addition, when the elastic modulus of the optical film is high, the occurrence of scratches and wrinkles is easily suppressed. In addition, when the YI value of the optical film is low, the transparency and visibility of the film are easily improved. The halogen atom is preferably a fluorine atom. Examples of fluorine-containing substituents that are preferable for containing fluorine atoms in the polyimide resin include a fluoro group and a trifluoromethyl group.
[0056] The content of halogen atoms in the polyimide resin is preferably 1 to 40 mass%, more preferably 5 to 40 mass%, and further preferably 5 to 30 mass%, based on the mass of the polyimide resin. When the content of halogen atoms is equal to or more than the above lower limit, the YI value of the optical film is easily reduced and the breaking strain and elastic modulus are easily increased. When the content of halogen atoms is equal to or less than the above upper limit, synthesis is facilitated.
[0057] The imidization rate of the polyimide resin is preferably 90% or more, more preferably 93% or more, and even more preferably 96% or more, and is usually 100% or less. From the viewpoint of easily improving the optical properties of the optical film, it is preferable that the imidization rate is equal to or higher than the above lower limit. The imidization rate indicates the ratio of the molar amount of imide bonds in the polyimide resin to twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide resin. In addition, when the polyimide resin contains a tricarboxylic acid compound, it indicates the ratio of the molar amount of imide bonds in the polyimide resin to the sum of twice the molar amount of the constituent units derived from the tetracarboxylic acid compound in the polyimide resin and the molar amount of the constituent units derived from the tricarboxylic acid compound. In addition, the imidization rate can be determined by IR method, NMR method, etc.
[0058] In one embodiment of the present invention, the polyimide-based resin contained in the optical film is preferably 40 mass % or more, more preferably 50 mass % or more, even more preferably 60 mass % or more, particularly preferably 80 mass % or more, and preferably 100 mass % or less, based on the mass of the optical film.
[0059] <Method of manufacturing polyimide resin> The method for producing the polyimide resin of the present invention is not particularly limited. In one embodiment of the present invention, the polyimide resin containing the constitutional unit represented by formula (1) can be produced by a method including a step of reacting a diamine compound with a tetracarboxylic acid compound to obtain a polyamic acid, and a step of imidizing the polyamic acid. In addition to the tetracarboxylic acid compound, a tricarboxylic acid compound may also be reacted.
[0060] The tetracarboxylic acid compound used in the production of the polyimide resin is at least a compound represented by the formula (X): [ka] [In formula (X), R 1 ~R 5 , n and m are R in formula (3), 1 ~R 5 , n and m are the same. and a compound represented by formula (Y): [ka] [In formula (Y), B, R 7 and t are B and R in formula (5), respectively. 7 and t] It is preferable that the compound contains a compound represented by the formula:
[0061] The compound represented by formula (X) may be obtained by a conventional method, for example, by reacting trimellitic anhydride or a derivative thereof with an aromatic diol, or a commercially available product may be used.
[0062] The structural units represented by formula (1) and formula (30) are usually derived from a diamine compound and a tetracarboxylic acid compound. The structural unit represented by formula (31) is usually derived from a diamine compound and a tricarboxylic acid compound.
[0063] The tetracarboxylic acid compound used in the synthesis of the polyimide resin may be an aromatic tetracarboxylic acid compound such as an aromatic tetracarboxylic acid dianhydride; or an aliphatic tetracarboxylic acid compound such as an aliphatic tetracarboxylic acid dianhydride. The tetracarboxylic acid compound may be used alone or in combination of two or more. The tetracarboxylic acid compound may be a dianhydride or a tetracarboxylic acid compound analog such as an acid chloride compound.
[0064] Specific examples of aromatic tetracarboxylic dianhydrides include non-condensed polycyclic aromatic tetracarboxylic dianhydrides, monocyclic aromatic tetracarboxylic dianhydrides, and condensed polycyclic aromatic tetracarboxylic dianhydrides. Examples of non-condensed polycyclic aromatic tetracarboxylic dianhydrides include an ester of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol (hereinafter sometimes referred to as TAHMBP), an ester of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP), an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP), and an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP). esters with 4,4'-biphenol, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter sometimes referred to as BPDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonate dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (hereinafter sometimes referred to as 6FDA), 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis( 2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride.In addition, an example of a monocyclic aromatic tetracarboxylic dianhydride is 1,2,4,5-benzenetetracarboxylic dianhydride (sometimes referred to as pyromellitic dianhydride, hereinafter sometimes referred to as PMDA), and an example of a condensed polycyclic aromatic tetracarboxylic dianhydride is 2,3,6,7-naphthalenetetracarboxylic dianhydride. Among these, preferred are esters of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol, esters of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol, esters of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarbo dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 6FDA, 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis( 2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, and 4,4'-(m-phenylenedioxy)diphthalic dianhydride are preferred, and a mixture of trimellitic anhydride and 2,2',3,3',5,5'-hexamethane dianhydride is more preferred. Examples of the esters include esters of 2,2',3,3'-tetramethyl-4,4'-biphenol and 2,2',3,3'-tetramethyl-4,4'-biphenol, esters of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 4,4'-oxydiphthalic dianhydride, BPDA, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 6FDA, bis(3,4-dicarboxyphenyl)methane dianhydride, and 4,4'-(p-phenylenedioxy)diphthalic dianhydride. These may be used alone or in combination of two or more.
[0065] Examples of the aliphatic tetracarboxylic dianhydride include cyclic or non-cyclic aliphatic tetracarboxylic dianhydrides. The cyclic aliphatic tetracarboxylic dianhydride is a tetracarboxylic dianhydride having an alicyclic hydrocarbon structure, and specific examples thereof include cycloalkane tetracarboxylic dianhydrides such as 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-cyclobutane tetracarboxylic dianhydride, and 1,2,3,4-cyclopentane tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride, and positional isomers thereof. These can be used alone or in combination of two or more. Specific examples of the non-cyclic aliphatic tetracarboxylic dianhydride include 1,2,3,4-butane tetracarboxylic dianhydride and 1,2,3,4-pentane tetracarboxylic dianhydride, and the like, and these can be used alone or in combination of two or more. Furthermore, a cyclic aliphatic tetracarboxylic acid dianhydride and a non-cyclic aliphatic tetracarboxylic acid dianhydride may be used in combination.
[0066] Among the above-mentioned tetracarboxylic dianhydrides, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, preferred are esters of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol, esters of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol, esters of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid, and the like. Preferred are acid dianhydrides, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 6FDA, and mixtures thereof, and more preferred are esters of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol, esters of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol, esters of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 6FDA, and mixtures thereof.
[0067] Examples of diamine compounds used in the synthesis of polyimide resins include aliphatic diamines, aromatic diamines, and mixtures thereof. In this embodiment, the term "aromatic diamine" refers to a diamine in which an amino group is directly bonded to an aromatic ring, and may include an aliphatic group or other substituents in a part of its structure. The aromatic ring may be a single ring or a condensed ring, and examples include a benzene ring, a naphthalene ring, an anthracene ring, and a fluorene ring, but are not limited to these. Among these, a benzene ring is preferable. The term "aliphatic diamine" refers to a diamine in which an amino group is directly bonded to an aliphatic group, and may include an aromatic ring or other substituents in a part of its structure.
[0068] Examples of the aliphatic diamine include acyclic aliphatic diamines such as hexamethylenediamine, and cyclic aliphatic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine, and 4,4'-diaminodicyclohexylmethane. These can be used alone or in combination of two or more.
[0069] Examples of the aromatic diamine include aromatic diamines having one aromatic ring, such as p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-xylylenediamine, p-xylylenediamine, 1,5-diaminonaphthalene, and 2,6-diaminonaphthalene; 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and the like. Examples of aromatic diamines having two or more aromatic rings include aromatic diamines having two or more aromatic rings, such as 2,2-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl (hereinafter sometimes referred to as TFMB), 4,4'-(hexafluoropropylidene)dianiline (hereinafter sometimes referred to as 6FDAM), 4,4'-bis(4-aminophenoxy)biphenyl, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, and 9,9-bis(4-amino-3-fluorophenyl)fluorene. These can be used alone or in combination of two or more.
[0070] The aromatic diamine is preferably 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, Examples of the 4,4'-diaminodiphenylmethane include 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, TFMB, 6FDAM, and 4,4'-bis(4-aminophenoxy)biphenyl. These can be used alone or in combination of two or more.
[0071] Among the above diamine compounds, from the viewpoint of easily improving the breaking strain, elastic modulus, and transparency of the optical film and easily reducing the thermal expansion coefficient, more preferred are one or more selected from the group consisting of 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl (TFMB), 4,4'-bis(4-aminophenoxy)biphenyl, 6FDAM, and 4,4'-diaminodiphenyl ether, and even more preferred are TFMB and / or 6FDAM.
[0072] The polyimide resin may be a resin obtained by further reacting, in addition to the tetracarboxylic acid compound used in the synthesis of the resin, other tetracarboxylic acids and tricarboxylic acids, as well as their anhydrides and derivatives, within the range that does not impair various physical properties of the optical film.
[0073] Other tetracarboxylic acids include water adducts of the anhydrides of the above tetracarboxylic acid compounds.
[0074] Examples of tricarboxylic acid compounds include aromatic tricarboxylic acids, aliphatic tricarboxylic acids, and their related acid chloride compounds, acid anhydrides, etc., and two or more of them may be used in combination.Specific examples include anhydride of 1,2,4-benzenetricarboxylic acid; 2,3,6-naphthalenetricarboxylic-2,3-anhydride; and a compound in which phthalic anhydride and benzoic acid are linked by a single bond, -O-, -CH2-, -C(CH3)2-, -C(CF3)2-, -SO2-, or a phenylene group.
[0075] In the production of a polyimide resin, the amounts of the diamine compound, tetracarboxylic acid compound and tricarboxylic acid compound used can be appropriately selected depending on the desired ratio of each structural unit of the resin. In a preferred embodiment of the present invention, the amount of the diamine compound used is preferably 0.94 mol or more, more preferably 0.96 mol or more, even more preferably 0.98 mol or more, particularly preferably 0.99 mol or more, and is preferably 1.20 mol or less, more preferably 1.10 mol or less, even more preferably 1.05 mol or less, particularly preferably 1.02 mol or less, relative to 1 mol of the tetracarboxylic acid compound. When the amount of the diamine compound used relative to the tetracarboxylic acid compound is within the above range, the Mw of the polyimide resin tends to increase, and the transparency, elastic modulus, and breaking strain of the optical film are easily increased, and the thermal expansion coefficient is easily reduced.
[0076] The reaction temperature between the diamine compound and the tetracarboxylic acid compound is not particularly limited and may be, for example, 5 to 200° C., and the reaction time is also not particularly limited and may be, for example, about 30 minutes to 72 hours. In a preferred embodiment of the present invention, the reaction temperature is preferably 5 to 50° C., more preferably 5 to 40° C., and even more preferably 5 to 25° C., and the reaction time is preferably 3 to 24 hours, and more preferably 5 to 20 hours. With such a reaction temperature and reaction time, the Mw of the polyimide resin tends to increase, and the transparency, elastic modulus, and breaking strain of the optical film are easily increased, and the thermal expansion coefficient is easily reduced.
[0077] The reaction between the diamine compound and the tetracarboxylic acid compound is preferably carried out in a solvent. The solvent is not particularly limited as long as it does not affect the reaction, and examples of the solvent include alcohol-based solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester-based solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone (hereinafter sometimes referred to as GBL), γ-valerolactone, propylene glycol methyl ether acetate, and ethyl lactate; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, and 2-heptanone. Examples of suitable solvents include ketone-based solvents such as methyl isobutyl ketone, pentane, hexane, heptane, and other aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents such as ethylcyclohexane, toluene, xylene, and other aromatic hydrocarbon solvents, nitrile-based solvents such as acetonitrile, ether-based solvents such as tetrahydrofuran and dimethoxyethane, chlorine-containing solvents such as chloroform and chlorobenzene, amide-based solvents such as N,N-dimethylacetamide (hereinafter sometimes referred to as DMAc), N,N-dimethylformamide (hereinafter sometimes referred to as DMF), and other sulfur-containing solvents, such as dimethylsulfone, dimethylsulfoxide, and sulfolane, carbonate-based solvents such as ethylene carbonate and propylene carbonate, and combinations thereof. Among these, amide-based solvents can be preferably used from the viewpoint of solubility. In a preferred embodiment of the present invention, the solvent used in the reaction is preferably a solvent that has been thoroughly dehydrated to a water content of 700 ppm or less. When such a solvent is used, the Mw of the polyimide resin tends to increase, and the transparency, elastic modulus, and breaking strain of the optical film are easily increased, and the thermal expansion coefficient is easily reduced.
[0078] The reaction between the diamine compound and the tetracarboxylic acid compound may be carried out under an inert atmosphere such as a nitrogen atmosphere or an argon atmosphere or under reduced pressure, if necessary, and is preferably carried out under the inert atmosphere while stirring in a strictly controlled dehydrated solvent. Under such conditions, the Mw of the polyimide resin tends to increase, and the transparency, elastic modulus, and breaking strain of the optical film are easily increased, and the thermal expansion coefficient is easily reduced.
[0079] Examples of the imidization catalyst used in the imidization step include aliphatic amines such as tripropylamine, dibutylpropylamine, and ethyldibutylamine; alicyclic amines (monocyclic) such as N-ethylpiperidine, N-propylpiperidine, N-butylpyrrolidine, N-butylpiperidine, and N-propylhexahydroazepine; azabicyclo[2.2.1]heptane, azabicyclo[3.2.1]octane, azabicyclo[2.2.2]octane, and azabicyclo[2.2.3]octane. [3.2.2] Alicyclic amines (polycyclic) such as nonane; and aromatic amines such as pyridine, 2-methylpyridine (2-picoline), 3-methylpyridine (3-picoline), 4-methylpyridine (4-picoline), 2-ethylpyridine, 3-ethylpyridine, 4-ethylpyridine, 2,4-dimethylpyridine, 2,4,6-trimethylpyridine, 3,4-cyclopentenopyridine, 5,6,7,8-tetrahydroisoquinoline, and isoquinoline. In addition, from the viewpoint of facilitating the imidization reaction, it is preferable to use an acid anhydride together with the imidization catalyst. Examples of the acid anhydride include conventional acid anhydrides used in imidization reactions, and specific examples thereof include aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, and butyric anhydride, and aromatic acid anhydrides such as phthalic acid.
[0080] In a preferred embodiment of the present invention, it is preferable to carry out the imidization step stepwise and raise the temperature to an optimal reaction temperature. By carrying out the imidization stepwise, it is possible to suppress the decomposition of the resin and to easily increase the Mw of the polyimide resin, so that it is easy to increase the transparency, elastic modulus, and breaking strain of the optical film, and it is easy to reduce the thermal expansion coefficient. The reaction temperature for raising the temperature in the imidization step stepwise is preferably 40 to 85°C, more preferably 45 to 80°C. When the reaction temperature is within the above range, the imidization reaction tends to proceed sufficiently, and the molecular weight tends to increase sufficiently. The reaction time is preferably 30 minutes to 10 hours, more preferably 30 minutes to 5 hours. When the reaction time is within the above range, on the contrary, the decomposition of the resin does not occur and the molecular weight does not increase sufficiently, and the imidization rate is low, so that the molecular weight does not tend to be reduced in the subsequent steps. In addition to the above-mentioned synthesis conditions, by controlling the imidization step in this way, a resin having a large weight average molecular weight can be obtained, and it is easy to increase the transparency, elastic modulus, and breaking strain of the optical film, and it is easy to reduce the thermal expansion coefficient.
[0081] The polyimide resin may be isolated (separated and purified) by a conventional method, for example, a separation means such as filtration, concentration, extraction, crystallization, recrystallization, column chromatography, or a combination of these. In a preferred embodiment, the resin can be isolated by adding a large amount of alcohol such as methanol to a reaction solution containing the resin to precipitate the resin, and then concentrating, filtering, drying, or the like.
[0082] [Optical Film] The present invention includes an optical film containing the polyimide resin of the present invention. The optical film of the present invention contains the polyimide resin, and therefore can achieve both high breaking strain and low thermal expansion coefficient. Therefore, the polyimide resin and the optical film of the present invention can be suitably used as materials for flexible display devices. In this specification, transparency can be evaluated by total light transmittance and haze, and increasing or improving transparency means increasing total light transmittance and decreasing haze.
[0083] The optical film of the present invention can exhibit a high breaking strain. The breaking strain of the optical film is preferably 30% or more, more preferably 31% or more. The upper limit of the breaking strain is usually 80% or less. The breaking strain can be measured using a tensile tester. More specifically, the breaking strain can be determined by obtaining a stress-strain curve (SS curve) using a tensile tester under conditions of a chuck distance of 50 mm and a pulling speed of 10 mm / min, and the amount of strain at which the film breaks can be calculated from the curve, and can be measured, for example, by the method described in the examples.
[0084] The optical film of the present invention can exhibit a low coefficient of thermal expansion (sometimes referred to as CTE). The coefficient of thermal expansion of the optical film is preferably 30 ppm / K or less, more preferably 28 ppm / K or less, further preferably 25 ppm / K or less, and usually 0 ppm / K or more. The coefficient of thermal expansion can be measured using a thermomechanical analyzer. More specifically, the coefficient of thermal expansion can be measured by applying a load of the film thickness (μm)×0.5 g, once heating the film to 150° C. at 5° C. / min, then cooling the film to 20° C., and further heating the film at 5° C. / min, obtaining a TMA curve at the second heating, and taking the average value between 100 and 200° C., for example, by the method described in the Examples.
[0085] In a preferred embodiment of the present invention, the total light transmittance of the optical film of the present invention, preferably the total light transmittance at a thickness of 50 μm, is preferably 85% or more, more preferably 88% or more, even more preferably 89% or more, particularly preferably 90% or more, and most preferably 91% or more. If the total light transmittance is equal to or more than the above lower limit, the transparency of the optical film can be improved, and when used, for example, as a front panel of a display device, high visibility can be achieved. The upper limit of the total light transmittance is usually 100% or less. In addition, the total light transmittance can be measured using a haze computer in accordance with JIS K 7105:1981, and can be measured, for example, by the method described in the Examples. In addition, in this specification, the total light transmittance can also be the total light transmittance in the thickness range of the optical film of the present invention.
[0086] In a preferred embodiment of the present invention, the haze of the optical film of the present invention, preferably the haze at a thickness of 50 μm, is preferably 2.0% or less, more preferably 1.5% or less, even more preferably 1.0% or less, even more preferably 0.8% or less, particularly preferably 0.5% or less, most preferably 0.3% or less, and usually 0% or more. When the haze of the optical film is below the upper limit, the transparency of the optical film can be improved, and when used, for example, as a front panel of a display device, high visibility can be achieved. The haze can be measured using a haze computer or the like in accordance with JIS K 7136:2000, for example, by the method described in the Examples. In addition, in this specification, the haze can also be the haze in the thickness range of the optical film of the present invention.
[0087] In a preferred embodiment of the present invention, the YI value of the optical film of the present invention is preferably 3.0 or less, more preferably 2.8 or less, and even more preferably 2.5 or less, and is usually -5 or more, preferably -2 or more. When the YI value of the optical film is equal to or less than the above upper limit, the transparency of the optical film can be improved, and when the optical film is used as a front panel of a display device, high visibility can be achieved. The YI value can be calculated based on the formula YI=100×(1.2769X-1.0592Z) / Y by measuring the transmittance of light at 300 to 800 nm using an ultraviolet-visible-near infrared spectrophotometer to obtain tristimulus values (X, Y, Z). For example, the YI value can be calculated by the method described in the Examples.
[0088] In a preferred embodiment of the present invention, the optical film of the present invention can exhibit a high elastic modulus. The elastic modulus of the optical film of the present invention is preferably 3.5 GPa or more, more preferably 4.0 GPa or more, and even more preferably 4.5 GPa or more, and is usually 15 GPa or less. When the elastic modulus is equal to or more than the above lower limit, deformation of the optical film is easily suppressed and durability is easily improved. The elastic modulus can be measured using a tensile tester. More specifically, the elastic modulus can be determined by determining a stress-strain curve (SS curve) using a tensile tester under conditions of a chuck distance of 50 mm and a tensile speed of 10 mm / min, and the slope of the curve can be measured, for example, by the method described in the Examples. The elastic modulus is a value at 25°C.
[0089] The total light transmittance and haze change depending on the thickness of the optical film, and the greater the thickness, the lower the total light transmittance and the higher the haze. That is, it is difficult to produce an optical film with high total light transmittance and low haze in a thick film. On the other hand, in a preferred embodiment of the present invention, the optical film of the present invention has a high level of transparency, so that even if the thickness is relatively large, it can exhibit high total light transmittance and low haze. Therefore, the optical film of the present invention can have a thickness of preferably 35 μm or more, more preferably 40 μm or more, and even more preferably 45 μm or more. In addition, the upper limit of the thickness of the optical film of the present invention is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. The thickness of the optical film can be measured using a film thickness meter or the like, for example, by the method described in the Examples.
[0090] <Additives> The optical film of the present invention may contain at least one filler in addition to the polyimide resin. Examples of the filler include organic particles and inorganic particles, and preferably inorganic particles. Examples of the inorganic particles include metal oxide particles such as silica, zirconia, alumina, titania, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide (ITO), antimony oxide, and cerium oxide, and metal fluoride particles such as magnesium fluoride and sodium fluoride. Among these, from the viewpoint of easily achieving both the elastic modulus and transparency of the optical film, silica particles, zirconia particles, and alumina particles are preferred, and silica particles are more preferred. These fillers can be used alone or in combination of two or more.
[0091] The average primary particle diameter of the filler, preferably silica particles, is usually 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more, even more preferably 15 nm or more, particularly preferably 20 nm or more, and preferably 100 nm or less, more preferably 90 nm or less, even more preferably 80 nm or less, even more preferably 70 nm or less, particularly preferably 60 nm or less, even more particularly preferably 50 nm or less, and most preferably 40 nm or less. When the average primary particle diameter of the filler, preferably silica particles, is within the above range, it is easy to improve the elastic modulus of the optical film and easy to reduce the thermal expansion coefficient. In addition, it is easy to suppress the aggregation of the filler, preferably silica particles, and improve the optical properties of the obtained optical film. The average primary particle diameter of the filler can be measured by the BET method. The average primary particle diameter may be measured by image analysis of a transmission electron microscope or a scanning electron microscope.
[0092] When the optical film of the present invention contains a filler, preferably silica particles, the content of the filler is usually 0.1% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, even more preferably 20% by mass or more, particularly preferably 30% by mass or more, and preferably 60% by mass or less, based on the mass of the optical film. When the content of the filler is equal to or more than the lower limit, the elastic modulus and the thermal expansion coefficient of the optical film are easily improved and the thermal expansion coefficient is easily reduced. When the content of the filler is equal to or less than the upper limit, the optical properties of the optical film are easily improved.
[0093] The optical film of the present invention may further contain an ultraviolet absorber. The ultraviolet absorber may be appropriately selected from those that are commonly used as ultraviolet absorbers in the field of resin materials. The ultraviolet absorber may contain a compound that absorbs light with a wavelength of 400 nm or less. Examples of the ultraviolet absorber include at least one compound selected from the group consisting of benzophenone-based compounds, salicylate-based compounds, benzotriazole-based compounds, and triazine-based compounds. The ultraviolet absorbers may be used alone or in combination of two or more. When the optical film contains an ultraviolet absorber, deterioration of the resin is suppressed, so that visibility can be improved when the optical film is applied to an image display device or the like. In this specification, the term "based compound" refers to a derivative of the compound to which the term "based compound" is attached. For example, the term "benzophenone-based compound" refers to a compound having benzophenone as a parent skeleton and a substituent bonded to benzophenone.
[0094] When the optical film contains an ultraviolet absorbing agent, the content of the ultraviolet absorbing agent is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 3 mass% or more, and is preferably 10 mass% or less, more preferably 8 mass% or less, and even more preferably 6 mass% or less, relative to the mass of the optical film. The suitable content varies depending on the ultraviolet absorbing agent used, but adjusting the content of the ultraviolet absorbing agent so that the light transmittance at 400 nm is about 20 to 60% increases the light resistance of the optical film and also makes it easy to increase the transparency.
[0095] The optical film of the present invention may further contain other additives other than the filler and the UV absorber. Examples of the other additives include antioxidants, release agents, stabilizers, bluing agents, flame retardants, pH adjusters, silica dispersants, lubricants, thickeners, and leveling agents. When other additives are contained, the content thereof may be preferably 0.001 to 20% by mass, more preferably 0.01 to 15% by mass, and even more preferably 0.1 to 10% by mass, based on the mass of the optical film.
[0096] The use of the optical film of the present invention is not particularly limited, and it may be used for various purposes. As described above, the optical film of the present invention may be a single layer or a laminate, and the optical film of the present invention may be used as it is, or may be used as a laminate with other films. When the optical film is a laminate, all layers laminated on one side or both sides of the optical film are referred to as the optical film.
[0097] When the optical film of the present invention is a laminate, it is preferable that the optical film has one or more functional layers on at least one surface thereof. Examples of the functional layer include a hard coat layer, a primer layer, a gas barrier layer, an ultraviolet absorbing layer, an adhesive layer, a hue adjusting layer, and a refractive index adjusting layer. The functional layers can be used alone or in combination of two or more kinds.
[0098] The thickness of the hard coat layer is not particularly limited, and may be, for example, 2 to 100 μm. When the thickness of the hard coat layer is within the above range, the impact resistance can be increased, and the bending resistance is not likely to decrease, and the problem of curling due to curing shrinkage tends to be unlikely to occur. The hard coat layer can be formed by curing a hard coat composition containing a reactive material that can form a crosslinked structure by irradiation with active energy rays or by applying thermal energy, and is preferably formed by irradiation with active energy rays. The active energy rays are defined as energy rays that can decompose a compound that generates active species to generate active species, and examples of such rays include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams, and preferably ultraviolet rays. The hard coat composition contains at least one polymer of a radical polymerizable compound and a cationic polymerizable compound.
[0099] The radical polymerizable compound is a compound having a radical polymerizable group. The radical polymerizable group of the radical polymerizable compound may be any functional group capable of generating a radical polymerization reaction, and may include a group containing a carbon-carbon unsaturated double bond, and specifically includes a vinyl group and a (meth)acryloyl group. When the radical polymerizable compound has two or more radical polymerizable groups, these radical polymerizable groups may be the same or different. The number of radical polymerizable groups that the radical polymerizable compound has in one molecule is preferably 2 or more from the viewpoint of improving the hardness of the hard coat layer. From the viewpoint of high reactivity, the radical polymerizable compound is preferably a compound having a (meth)acryloyl group, and specifically includes compounds called polyfunctional acrylate monomers having 2 to 6 (meth)acryloyl groups in one molecule, and oligomers having several (meth)acryloyl groups in the molecule and having a molecular weight of several hundred to several thousand, called epoxy (meth)acrylates, urethane (meth)acrylates, and polyester (meth)acrylates, and preferably includes one or more types selected from epoxy (meth)acrylates, urethane (meth)acrylates, and polyester (meth)acrylates.
[0100] The cationic polymerizable compound is a compound having a cationic polymerizable group such as an epoxy group, an oxetanyl group, a vinyl ether group, etc. The number of cationic polymerizable groups that the cationic polymerizable compound has in one molecule is preferably 2 or more, more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer. Among the cationic polymerizable compounds, compounds having at least one of epoxy and oxetanyl groups as cationic polymerizable groups are preferred. Cyclic ether groups such as epoxy and oxetanyl groups are preferred because they cause little shrinkage during polymerization. Among cyclic ether groups, compounds having epoxy groups are easily available in a variety of structures, and have the advantage that they do not adversely affect the durability of the obtained hard coat layer, and the compatibility with the radical polymerizable compound is easy to control. Among cyclic ether groups, oxetanyl groups tend to have a higher degree of polymerization than epoxy groups, and have the advantage of accelerating the network formation rate obtained from the cationic polymerizable compound of the obtained hard coat layer, and forming an independent network without leaving unreacted monomers in the film even in the region where the radical polymerizable compound is mixed. Examples of the cationically polymerizable compound having an epoxy group include alicyclic epoxy resins obtained by epoxidizing a polyglycidyl ether of a polyhydric alcohol having an alicyclic ring or a compound containing a cyclohexene ring or a cyclopentene ring with a suitable oxidizing agent such as hydrogen peroxide or a peracid; aliphatic epoxy resins such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts, polyglycidyl esters of aliphatic long-chain polybasic acids, and homopolymers and copolymers of glycidyl (meth)acrylate; glycidyl ethers produced by reacting bisphenols such as bisphenol A, bisphenol F, and hydrogenated bisphenol A, or derivatives thereof such as alkylene oxide adducts or caprolactone adducts, with epichlorohydrin, and glycidyl ether-type epoxy resins derived from bisphenols such as novolak epoxy resins.
[0101] The hard coat composition may further include a polymerization initiator. The polymerization initiator may be a radical polymerization initiator, a cationic polymerization initiator, a radical and cationic polymerization initiator, etc., and may be appropriately selected and used. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating, generating radicals or cations to promote radical polymerization and cationic polymerization. The radical polymerization initiator may be any initiator capable of releasing a substance that initiates radical polymerization by at least one of irradiation with active energy rays and heating. For example, examples of thermal radical polymerization initiators include organic peroxides such as hydrogen peroxide and perbenzoic acid, and azo compounds such as azobisbutyronitrile. Active energy ray radical polymerization initiators include Type 1 radical polymerization initiators, which generate radicals by molecular decomposition, and Type 2 radical polymerization initiators, which coexist with tertiary amines to generate radicals through a hydrogen abstraction reaction. These are used alone or in combination. The cationic polymerization initiator may be any one that can release a substance that initiates cationic polymerization by at least one of active energy ray irradiation and heating. As the cationic polymerization initiator, aromatic iodonium salts, aromatic sulfonium salts, cyclopentadienyl iron (II) complexes, etc. can be used. These can initiate cationic polymerization by either active energy ray irradiation or heating, or both, depending on the difference in structure.
[0102] The polymerization initiator can be preferably contained in an amount of 0.1 to 10% by mass relative to 100% by mass of the entire hard coat composition. When the content of the polymerization initiator is within the above range, curing can be sufficiently promoted, the mechanical properties and adhesive strength of the finally obtained coating film can be in a good range, and poor adhesive strength, cracking, and curling due to cure shrinkage tend to be unlikely to occur.
[0103] The hard coat composition may further include at least one selected from the group consisting of a solvent and an additive. The solvent can dissolve or disperse the polymerizable compound and the polymerization initiator, and any solvent known in the art as a solvent for hard coat compositions can be used as long as it does not impair the effects of the present invention. The additives may further include inorganic particles, leveling agents, stabilizers, surfactants, antistatic agents, lubricants, antifouling agents, and the like.
[0104] The ultraviolet absorbing layer is a layer having the function of absorbing ultraviolet rays, and is composed of a main material selected from, for example, an ultraviolet curing type transparent resin, an electron beam curing type transparent resin, and a thermosetting type transparent resin, and an ultraviolet absorbing agent dispersed in this main material.
[0105] The adhesive layer is a layer having an adhesive function, and has a function of adhering the optical film to other members. As a material for forming the adhesive layer, a commonly known material can be used. For example, a thermosetting resin composition or a photocurable resin composition can be used. In this case, the thermosetting resin composition or the photocurable resin composition can be polymerized and cured by supplying energy thereto afterwards.
[0106] The adhesive layer may be a layer called a pressure-sensitive adhesive (PSA), which is attached to an object by pressing. The pressure-sensitive adhesive may be a pressure-sensitive adhesive that is "a substance that has adhesiveness at room temperature and adheres to an adherend with light pressure" (JIS K 6800), or it may be a capsule-type adhesive that is "an adhesive that contains a specific component in a protective film (microcapsules) and can maintain stability until the film is destroyed by an appropriate means (pressure, heat, etc.)" (JIS K 6800).
[0107] The hue adjustment layer is a layer having a function of adjusting the hue, and can adjust the hue of the optical film to a desired hue. The hue adjustment layer is, for example, a layer containing a resin and a colorant. Examples of the colorant include inorganic pigments such as titanium oxide, zinc oxide, red iron oxide, titanium oxide-based calcined pigments, ultramarine, cobalt aluminate, and carbon black; organic pigments such as azo compounds, quinacridone compounds, anthraquinone compounds, perylene compounds, isoindolinone compounds, phthalocyanine compounds, quinophthalone compounds, threne compounds, and diketopyrrolopyrrole compounds; extender pigments such as barium sulfate and calcium carbonate; and dyes such as basic dyes, acid dyes, and mordant dyes.
[0108] The refractive index adjusting layer is a layer having a function of adjusting the refractive index, and has a refractive index different from that of a single-layer optical film, and can impart a predetermined refractive index to the optical film. The refractive index adjusting layer may be, for example, a resin layer containing an appropriately selected resin and, if necessary, a pigment, or may be a thin metal film. Examples of pigments for adjusting the refractive index include silicon oxide, aluminum oxide, antimony oxide, tin oxide, titanium oxide, zirconium oxide, and tantalum oxide. The average primary particle diameter of the pigment may be 0.1 μm or less. By setting the average primary particle diameter of the pigment to 0.1 μm or less, diffuse reflection of light passing through the refractive index adjusting layer can be prevented, and a decrease in transparency can be prevented. Examples of metals used in the refractive index adjusting layer include metal oxides or metal nitrides such as titanium oxide, tantalum oxide, zirconium oxide, zinc oxide, tin oxide, silicon oxide, indium oxide, titanium oxynitride, titanium nitride, silicon oxynitride, and silicon nitride.
[0109] In one embodiment of the present invention, the optical film may have a protective film on at least one side, i.e., on one side or both sides. For example, when the optical film has a functional layer on one side, the protective film may be laminated on the surface on the optical film side or the surface on the functional layer side, or may be laminated on both the optical film side and the functional layer side. When the optical film has a functional layer on both sides, the protective film may be laminated on the surface on one functional layer side, or may be laminated on the surfaces on both functional layer sides. The protective film is a film for temporarily protecting the surface of the optical film or the functional layer, and is not particularly limited as long as it is a peelable film that can protect the surface of the optical film or the functional layer. Examples of the protective film include polyester-based resin films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin-based resin films such as polyethylene and polypropylene films, and acrylic resin films, and are preferably selected from the group consisting of polyolefin-based resin films, polyethylene terephthalate-based resin films, and acrylic resin films. When the optical film has two protective films, each protective film may be the same or different.
[0110] The thickness of the protective film is not particularly limited, but is usually 10 to 120 μm, preferably 15 to 110 μm, and more preferably 20 to 100 μm. When the optical film has two protective films, the thicknesses of the protective films may be the same or different.
[0111] [Method for producing optical film] The optical film of the present invention can be produced, but is not limited to, by the following process, for example: (a) preparing a liquid containing the polyimide-based resin (sometimes referred to as a resin varnish) (varnish preparation step); (b) a step of applying a resin varnish to a substrate to form a coating film (a coating step); and (c) A process of drying the applied liquid (coating film) to form an optical film (optical film formation process). The composition can be produced by a method comprising the steps of:
[0112] In the varnish preparation step, the polyimide resin is dissolved in a solvent, and the additives are added as necessary, followed by stirring and mixing to prepare a resin varnish.
[0113] The solvent used in preparing the resin varnish is not particularly limited as long as it can dissolve the resin. Examples of such solvents include amide-based solvents such as DMAc and DMF; lactone-based solvents such as GBL and γ-valerolactone; sulfur-containing solvents such as dimethylsulfone, dimethylsulfoxide, and sulfolane; carbonate-based solvents such as ethylene carbonate and propylene carbonate; and combinations thereof. Among these, amide-based solvents or lactone-based solvents are preferred. These solvents can be used alone or in combination of two or more. The resin varnish may also contain water, alcohol-based solvents, ketone-based solvents, acyclic ester-based solvents, ether-based solvents, and the like. The solid content concentration of the varnish is preferably 1 to 25% by mass, more preferably 5 to 15% by mass. In this specification, the solid content of the varnish refers to the total amount of components excluding the solvent from the varnish.
[0114] In the coating step, the varnish is applied onto the substrate to form a coating film by a known coating method, such as a wire bar coating method, a roll coating method such as reverse coating or gravure coating, a die coating method, a comma coating method, a lip coating method, a spin coating method, a screen coating method, a fountain coating method, a dipping method, a spray method, a drip molding method, etc.
[0115] In the optical film forming process, the coating film is dried and peeled off from the substrate to form an optical film. A drying process for drying the optical film may be performed after peeling. The coating film can be dried at a temperature of usually 50 to 350°C, preferably 50 to 230°C. In a preferred embodiment of the present invention, it is preferable to perform drying in stages. A varnish containing a high molecular weight resin tends to have a high viscosity, and it is generally difficult to obtain a uniform film, and a film with excellent transparency may not be obtained. Therefore, by performing drying in stages, the varnish containing a high molecular weight resin can be dried uniformly, and the transparency can be improved. If necessary, the coating film may be dried under an inert atmosphere. In addition, if the optical film is dried under vacuum conditions, fine air bubbles may be generated and remain in the film, which is a factor in reducing transparency, so it is preferable to perform drying under atmospheric pressure.
[0116] Examples of the substrate include a PET film, a PEN film, other polyimide-based resin or polyamide-based resin films, etc. Among them, from the viewpoint of excellent heat resistance, a PET film, a PEN film, etc. are preferred, and further, from the viewpoint of adhesion to the optical film and cost, a PET film is more preferred.
[0117] The optical film of the present invention can be suitably used as a front plate (hereinafter sometimes referred to as a window film) of a display device, particularly a flexible display device, particularly a rollable display or foldable display. That is, the optical film of the present invention is preferably a film for a front plate of a flexible display device. The front plate has a function of protecting the display element of a flexible display device. The flexible display device is a display device used with operations such as repeatedly folding and rolling an image display device. The front plate of a flexible display device used with such repeated folding operations is required to have high bending resistance. In addition, the front plate is also required to have high visibility. Compared with a film for a substrate of an image display device used inside the image display device, the front plate of an image display device, particularly a film for a front plate of a flexible display device, is required to have high visibility and high bending resistance. For example, the film of the present invention preferably has the total light transmittance, haze and / or YI value described above from the viewpoint of easily increasing visibility when used for the front plate of a flexible display device.
[0118] Examples of the display device include televisions, smartphones, mobile phones, car navigation systems, tablet PCs, portable game consoles, electronic paper, indicators, bulletin boards, watches, and wearable devices such as smart watches. Examples of the flexible display device include display devices having flexible characteristics, such as televisions, smartphones, mobile phones, and smart watches. Examples of the flexible display device include all image display devices having flexible characteristics, such as the above-mentioned rollable displays and foldable displays. The rollable display is an image display device in which the image display part including the front panel is wound up in a roll, and the image display part is pulled out and used in a flat or curved state, and an operation such as winding up in a roll is performed each time the display device is used. The foldable display is an image display device in which the image display part including the front panel is folded, and the image display part is opened and used in a flat or curved state, and an operation such as folding is performed each time the display device is used. Such an image display device in which operations such as winding and folding are repeatedly performed is called a flexible display device.
[0119] [Flexible display device] The present invention includes a flexible display device comprising the optical film of the present invention. The optical film of the present invention is preferably used as a front plate in a flexible display device, and the front plate may be called a window film. The flexible display device is composed of a laminate for a flexible display device and an organic EL display panel, and the laminate for a flexible display device is arranged on the viewing side of the organic EL display panel and is configured to be foldable. The laminate for a flexible display device may further contain a polarizing plate and a touch sensor, and although the order of lamination of these is arbitrary, it is preferable that the laminate is laminated in the order of a window film, a polarizing plate, a touch sensor, or a window film, a touch sensor, and a polarizing plate from the viewing side. If a polarizing plate is present on the viewing side of the touch sensor, the pattern of the touch sensor is less visible, and the visibility of the displayed image is improved, which is preferable. Each member can be laminated using an adhesive, a pressure-sensitive adhesive, or the like. In addition, a light-shielding pattern formed on at least one surface of any of the layers of the window film, the polarizing plate, and the touch sensor can be provided.
[0120] [Polarizing Plate] As described above, the flexible display device of the present invention preferably further comprises a polarizing plate, particularly a circular polarizing plate. The circular polarizing plate is a functional layer having a function of transmitting only right- or left-handed circularly polarized components by laminating a λ / 4 retardation plate on a linear polarizing plate. For example, the circular polarizing plate is used to convert external light into right-handed circularly polarized light, block the external light that is reflected by the organic EL panel and becomes left-handed circularly polarized light, and transmit only the light-emitting component of the organic EL, thereby suppressing the influence of reflected light and making the image easier to see. In order to achieve the circular polarization function, the absorption axis of the linear polarizing plate and the slow axis of the λ / 4 retardation plate theoretically need to be 45°, but in practice, it is 45±10°. The linear polarizing plate and the λ / 4 retardation plate do not necessarily need to be laminated adjacent to each other, and it is sufficient that the relationship between the absorption axis and the slow axis satisfies the above-mentioned range. It is preferable to achieve complete circular polarization at all wavelengths, but this is not necessarily required in practice, so the circular polarizing plate in the present invention also includes an elliptical polarizing plate. It is also preferable to further laminate a λ / 4 phase difference film on the viewing side of the linear polarizing plate to make the emitted light circularly polarized, thereby improving visibility when wearing polarized sunglasses.
[0121] A linear polarizing plate is a functional layer that transmits light vibrating in the transmission axis direction but blocks polarized light of vibration components perpendicular thereto. The linear polarizing plate may be a linear polarizer alone or a linear polarizer with a protective film attached to at least one surface of the linear polarizer. The thickness of the linear polarizing plate may be 200 μm or less, and is preferably 0.5 to 100 μm. When the thickness of the linear polarizing plate is within the above range, the flexibility of the linear polarizing plate tends not to decrease.
[0122] The linear polarizer may be a film-type polarizer produced by dyeing and stretching a polyvinyl alcohol (hereinafter sometimes abbreviated as PVA)-based film. A dichroic dye such as iodine is adsorbed to the PVA-based film oriented by stretching, or the dichroic dye is oriented by stretching in a state where it is adsorbed to PVA, and the film exhibits polarization performance. The production of the film-type polarizer may further include steps such as swelling, crosslinking with boric acid, washing with an aqueous solution, and drying. The stretching and dyeing steps may be performed on the PVA-based film alone, or may be performed in a state where it is laminated with another film such as polyethylene terephthalate. The thickness of the PVA-based film used is preferably 10 to 100 μm, and the stretching ratio is preferably 2 to 10 times. Another example of the polarizer is a liquid crystal coating type polarizer formed by coating a liquid crystal polarizing composition. The liquid crystal polarizing composition may contain a liquid crystal compound and a dichroic dye compound. The liquid crystal compound may have a property of exhibiting a liquid crystal state, and is preferably in a highly oriented state such as a smectic phase, since it can exhibit high polarization performance. The liquid crystal compound preferably has a polymerizable functional group. The dichroic dye compound is a dye that exhibits dichroism when aligned together with the liquid crystal compound, and may have a polymerizable functional group, or the dichroic dye itself may have liquid crystal properties. Any of the compounds contained in the liquid crystal polarizing composition has a polymerizable functional group. The liquid crystal polarizing composition may further include an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, etc. The liquid crystal polarizing layer is produced by applying a liquid crystal polarizing composition onto an alignment film to form a liquid crystal polarizing layer. The liquid crystal polarizing layer can be formed to have a smaller thickness than a film-type polarizer, and the thickness is preferably 0.5 to 10 μm, more preferably 1 to 5 μm.
[0123] The alignment film is produced, for example, by applying an alignment film-forming composition onto a substrate and imparting alignment by rubbing, polarized light irradiation, or the like. The alignment film-forming composition contains an alignment agent, and may further contain a solvent, a crosslinking agent, an initiator, a dispersant, a leveling agent, a silane coupling agent, or the like. Examples of the alignment agent include polyvinyl alcohols, polyacrylates, polyamic acids, and polyimides. When using an alignment agent that imparts alignment by polarized light irradiation, it is preferable to use an alignment agent that contains a cinnamate group. The Mw of the polymer used as the alignment agent is, for example, about 10,000 to 1,000,000. The thickness of the alignment film is preferably 5 to 10,000 nm, and more preferably 10 to 500 nm in terms of sufficient expression of alignment control force. The liquid crystal polarizing layer can be peeled off from the substrate and transferred to the substrate, or the substrate can be directly laminated. It is also preferable that the substrate serves as a transparent substrate for a protective film, a retardation plate, or a window film.
[0124] The protective film may be a transparent polymer film, and may be the same as the materials and additives used in the transparent substrate of the window film. The protective film may also be a coating type protective film obtained by applying and curing a cationic curing composition such as an epoxy resin or a radical curing composition such as an acrylate. The protective film may contain a plasticizer, an ultraviolet absorber, an infrared absorber, a colorant such as a pigment or dye, a fluorescent whitening agent, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc., as necessary. The thickness of the protective film is preferably 200 μm or less, more preferably 1 to 100 μm. When the thickness of the protective film is within the above range, the flexibility of the film tends not to decrease.
[0125] The λ / 4 retardation plate is a film that imparts a phase difference of λ / 4 in a direction perpendicular to the direction of propagation of incident light, i.e., in the in-plane direction of the film. The λ / 4 retardation plate may be a stretched retardation plate manufactured by stretching a polymer film such as a cellulose-based film, an olefin-based film, or a polycarbonate-based film. The λ / 4 retardation plate may contain a retardation regulator, a plasticizer, an ultraviolet absorber, an infrared absorber, a colorant such as a pigment or a dye, a fluorescent whitening agent, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc., as necessary. The thickness of the stretched retardation plate is preferably 200 μm or less, more preferably 1 to 100 μm. When the thickness of the stretched retardation plate is in the above range, the flexibility of the stretched retardation plate tends not to decrease. Another example of the λ / 4 retardation plate is a liquid crystal coating type retardation plate formed by coating a liquid crystal composition. The liquid crystal composition contains a liquid crystal compound that exhibits a liquid crystal state such as nematic, cholesteric, smectic, etc. The liquid crystal compound has a polymerizable functional group. The liquid crystal composition may further include an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, and the like. The liquid crystal coating type retardation plate can be produced by coating a liquid crystal composition on a base and curing it to form a liquid crystal retardation layer, similar to the liquid crystal polarizing layer. The liquid crystal coating type retardation plate can be formed thinner than the stretching type retardation plate. The thickness of the liquid crystal polarizing layer is preferably 0.5 to 10 μm, more preferably 1 to 5 μm. The liquid crystal-coated retardation plate can be peeled off from the substrate and transferred to the substrate, or the substrate can be directly laminated. It is also preferable that the substrate serves as a transparent substrate for a protective film, a retardation plate, or a window film.
[0126] Generally, there are many materials that exhibit larger birefringence at shorter wavelengths and smaller birefringence at longer wavelengths. In this case, since it is not possible to achieve a phase difference of λ / 4 in the entire visible light region, the in-plane phase difference is designed to be preferably 100 to 180 nm, more preferably 130 to 150 nm, so that it is λ / 4 around 560 nm where visibility is high. A reverse dispersion λ / 4 phase difference plate using a material having a birefringence wavelength dispersion characteristic reverse to that of normal is preferable in terms of good visibility. As such materials, for example, those described in JP-A-2007-232873 and JP-A-2010-30979 can be used as stretched phase difference plates and liquid crystal coating phase difference plates, respectively. As another method, a technique is known in which a wideband λ / 4 retardation plate is obtained by combining it with a λ / 2 retardation plate (for example, JP-A-10-90521). The λ / 2 retardation plate is also manufactured using the same materials and methods as the λ / 4 retardation plate. The combination of the stretched retardation plate and the liquid crystal coating retardation plate is arbitrary, but the thickness of either can be reduced by using the liquid crystal coating retardation plate. A method of laminating a positive C plate on the circularly polarizing plate to improve the visibility in oblique directions is known (for example, JP 2014-224837 A, etc.). The positive C plate may be a liquid crystal coating type retardation plate or a stretched type retardation plate. The retardation in the thickness direction of the retardation plate is preferably -200 to -20 nm, more preferably -140 to -40 nm.
[0127] [Touch sensor] As described above, the flexible display device of the present invention preferably further includes a touch sensor. The touch sensor is used as an input means. As the touch sensor, various types such as a resistive film type, a surface acoustic wave type, an infrared type, an electromagnetic induction type, and a capacitance type can be mentioned, and a capacitance type is preferably mentioned. The capacitive touch sensor is divided into an active area and a non-active area located on the periphery of the active area. The active area corresponds to a display area where a screen is displayed on a display panel and is an area where a user's touch is sensed, and the non-active area corresponds to a non-display area where a screen is not displayed on a display device. The touch sensor may include a substrate having a flexible characteristic, a sensing pattern formed in the active area of the substrate, and sensing lines formed in the non-active area of the substrate for connecting to an external driving circuit via the sensing pattern and a pad part. The substrate having a flexible characteristic may be made of the same material as the transparent substrate of the window film.
[0128] The sensing pattern may include a first pattern formed in a first direction and a second pattern formed in a second direction. The first pattern and the second pattern are arranged in different directions. The first pattern and the second pattern are formed in the same layer, and in order to sense a touch point, the first pattern and the second pattern must be electrically connected to each other. The first pattern is a form in which a plurality of unit patterns are connected to each other through joints, but the second pattern is a structure in which a plurality of unit patterns are separated from each other in an island form, so a separate bridge electrode is required to electrically connect the second pattern. A well-known transparent electrode may be applied to the electrode for connecting the second pattern. Examples of materials for the transparent electrode include indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), indium zinc tin oxide (IZTO), indium gallium zinc oxide (IGZO), cadmium tin oxide (CTO), PEDOT (poly(3,4-ethylenedioxythiophene)), carbon nanotubes (CNT), graphene, and metal wires, and preferably ITO. These may be used alone or in combination of two or more. There are no particular limitations on the metal used for the metal wire, and examples thereof include silver, gold, aluminum, copper, iron, nickel, titanium, selenium, and chromium, which may be used alone or in combination of two or more. The bridge electrode may be formed on an insulating layer on the sensing pattern, or the bridge electrode may be formed on a substrate, and an insulating layer and a sensing pattern may be formed thereon. The bridge electrode may be made of the same material as the sensing pattern, or may be made of molybdenum, silver, aluminum, copper, palladium, gold, platinum, zinc, tin, titanium, or an alloy of two or more of these materials. Since the first pattern and the second pattern must be electrically insulated, an insulating layer is formed between the sensing pattern and the bridge electrode. The insulating layer can be formed only between the joint of the first pattern and the bridge electrode, or can be formed as a layer covering the entire sensing pattern. In the case of a layer covering the entire sensing pattern, the bridge electrode can connect the second pattern through a contact hole formed in the insulating layer.
[0129] The touch sensor may further include an optical adjustment layer between the substrate and the electrode as a means for appropriately compensating for a difference in transmittance between a patterned region where a sensing pattern is formed and a non-patterned region where a sensing pattern is not formed, specifically, a difference in light transmittance caused by a difference in refractive index between these regions. The optical adjustment layer may include an inorganic insulating material or an organic insulating material. The optical adjustment layer may be formed by coating a photocurable composition including a photocurable organic binder and a solvent on the substrate. The photocurable composition may further include inorganic particles. The inorganic particles may increase the refractive index of the optical adjustment layer. The photocurable organic binder may contain, within the scope not impairing the effects of the present invention, a copolymer of each monomer, such as an acrylate monomer, a styrene monomer, a carboxylic acid monomer, etc. The photocurable organic binder may be, for example, a copolymer containing different repeating units, such as an epoxy group-containing repeating unit, an acrylate repeating unit, a carboxylic acid repeating unit, etc. Examples of the inorganic particles include zirconia particles, titania particles, and alumina particles. The photocurable composition may further include various additives such as a photopolymerization initiator, a polymerizable monomer, and a curing assistant.
[0130] [Adhesive layer] Each layer such as a window film, a circular polarizing plate, and a touch sensor forming the laminate for a flexible display device, and each layer including a linear polarizing plate, a λ / 4 retardation plate, and other film members can be bonded with an adhesive. Examples of the adhesive include commonly used adhesives such as water-based adhesives, organic solvent-based adhesives, solvent-free adhesives, solid adhesives, solvent-volatile adhesives, water-based solvent-volatile adhesives, moisture-curing adhesives, heat-curing adhesives, anaerobic curing adhesives, active energy ray-curing adhesives, curing agent mixed adhesives, hot melt adhesives, pressure-sensitive adhesives, pressure-sensitive adhesives, and re-moistening adhesives, and preferably water-based solvent-volatile adhesives, active energy ray-curing adhesives, and adhesives. The thickness of the adhesive layer can be appropriately adjusted according to the required adhesive strength, and is preferably 0.01 to 500 μm, more preferably 0.1 to 300 μm. The laminate for a flexible display device has a plurality of adhesive layers, and the thickness and type of each layer may be the same or different.
[0131] As the aqueous solvent volatilizing adhesive, a water-dispersed polymer such as a polyvinyl alcohol polymer, a water-soluble polymer such as starch, an ethylene-vinyl acetate emulsion, or a styrene-butadiene emulsion can be used as a base polymer. In addition to the base polymer and water, a crosslinking agent, a silane compound, an ionic compound, a crosslinking catalyst, an antioxidant, a dye, a pigment, an inorganic filler, an organic solvent, or the like may be blended. When bonding is performed using the aqueous solvent volatilizing adhesive, the aqueous solvent volatilizing adhesive is injected between the adherend layers, the adherend layers are laminated, and then the layers are dried to impart adhesiveness. When the aqueous solvent volatilizing adhesive is used, the thickness of the adhesive layer is preferably 0.01 to 10 μm, more preferably 0.1 to 1 μm. When the aqueous solvent volatilizing adhesive is used in a plurality of layers, the thickness and type of each layer may be the same or different.
[0132] The active energy ray curable adhesive can be formed by curing an active energy ray curable composition containing a reactive material that forms an adhesive layer by irradiating active energy rays. The active energy ray curable composition can contain at least one polymer of a radical polymerizable compound and a cationic polymerizable compound similar to those contained in the hard coat composition. The radical polymerizable compound can be the same compound as the radical polymerizable compound in the hard coat composition. The cationically polymerizable compound may be the same as the cationically polymerizable compound in the hard coat composition. As the cationic polymerizable compound used in the active energy ray curable composition, an epoxy compound is particularly preferred. It is also preferred to contain a monofunctional compound as a reactive diluent in order to reduce the viscosity of the adhesive composition.
[0133] The active energy ray composition may contain a monofunctional compound to reduce viscosity. Examples of the monofunctional compound include an acrylate monomer having one (meth)acryloyl group in one molecule, and a compound having one epoxy group or oxetanyl group in one molecule, such as glycidyl (meth)acrylate. The active energy ray composition may further contain a polymerization initiator. The polymerization initiator may include a radical polymerization initiator, a cationic polymerization initiator, a radical and cationic polymerization initiator, etc., and these may be appropriately selected and used. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating, generating radicals or cations to advance radical polymerization and cationic polymerization. In the description of the hard coat composition, an initiator that can initiate at least one of radical polymerization and cationic polymerization by active energy ray irradiation may be used. The active energy ray curable composition may further contain an ion scavenger, an antioxidant, a chain transfer agent, an adhesion imparting agent, a thermoplastic resin, a filler, a flow viscosity modifier, a plasticizer, an antifoaming agent, an additive, and a solvent. When two adherend layers are bonded by the active energy ray curable adhesive, the active energy ray curable composition is applied to either or both of the adherend layers, and then the layers are laminated together, and either or both of the adherend layers are irradiated with active energy rays to cure the layers, thereby bonding the layers together. When the active energy ray curable adhesive is used, the thickness of the adhesive layer is preferably 0.01 to 20 μm, more preferably 0.1 to 10 μm. When the active energy ray curable adhesive is used to form a plurality of adhesive layers, the thickness and type of each layer may be the same or different.
[0134] The adhesive is classified into acrylic adhesives, urethane adhesives, rubber adhesives, silicone adhesives, etc. according to the base polymer, and any of them can be used. In addition to the base polymer, the adhesive may contain a crosslinking agent, a silane compound, an ionic compound, a crosslinking catalyst, an antioxidant, a tackifier, a plasticizer, a dye, a pigment, an inorganic filler, etc. The components constituting the adhesive are dissolved and dispersed in a solvent to obtain an adhesive composition, and the adhesive composition is applied to a substrate and then dried to form an adhesive layer. The adhesive layer may be formed directly, or a layer formed separately on a substrate may be transferred. It is also preferable to use a release film to cover the adhesive surface before adhesion. When the active energy ray curable adhesive is used, the thickness of the adhesive layer is preferably 0.1 to 500 μm, more preferably 1 to 300 μm. When a plurality of layers of the adhesive are used, the thickness and type of each layer may be the same or different.
[0135] [Light blocking pattern] The light-shielding pattern can be applied as at least a part of the bezel or housing of the flexible display device. By hiding the wiring arranged at the edge of the flexible display device with the light-shielding pattern and making it difficult to be visually recognized, the visibility of the image is improved. The light-shielding pattern may be in the form of a single layer or a multi-layer. The color of the light-shielding pattern is not particularly limited, and may be various colors such as black, white, and metallic colors. The light-shielding pattern can be formed of a pigment for realizing the color and a polymer such as an acrylic resin, an ester resin, an epoxy resin, polyurethane, and silicone. These can also be used alone or as a mixture of two or more kinds. The light-shielding pattern can be formed by various methods such as printing, lithography, and inkjet. The thickness of the light-shielding pattern is preferably 1 to 100 μm, more preferably 2 to 50 μm. It is also preferable to impart a shape such as an inclination in the thickness direction of the light-shielding pattern.
Example
[0136] Hereinafter, the present invention will be described more specifically based on examples and comparative examples, but the present invention is not limited to the following examples. First, the measurement and evaluation methods will be described.
[0137] <Total light transmittance> In accordance with JIS K 7105:1981, the total light transmittance (Tt) of the optical films obtained in the examples and comparative examples was measured using a fully automatic direct reading haze computer HGM-2DP manufactured by Suga Test Instruments Co., Ltd.
[0138] <Haze> In accordance with JIS K 7136:2000, the optical films obtained in the examples and comparative examples were cut into a size of 30 mm × 30 mm, and the haze (%) was measured using a haze computer (manufactured by Suga Test Instruments Co., Ltd., "HGM-2DP").
[0139] <YI value> For the optical films obtained in the examples and comparative examples, the tristimulus values (X, Y, Z) were determined using an ultraviolet-visible-near infrared spectrophotometer (V-670 manufactured by JASCO Corporation), and the YI value was calculated by substituting the values into the following calculation formula. YI=100×(1.2769X-1.0592Z) / Y
[0140] <Elastic modulus, breaking strain> The elastic modulus and breaking strain of the optical films obtained in the examples and comparative examples were measured using an "Autograph AG-IS" manufactured by Shimadzu Corporation. The optical film was cut into a length and width of 10 mm to prepare a measurement sample, which was set in the device and a stress-strain curve (SS curve) was measured under conditions of a chuck distance of 50 mm and a pulling speed of 10 mm / min. The elastic modulus was calculated from the slope, and the amount of strain at which the film broke was calculated as the breaking strain.
[0141] <Measurement of coefficient of thermal expansion (CTE)> The CTE of the optical films obtained in the examples and comparative examples was measured using a thermomechanical analyzer "TMA / SS7100" manufactured by Hitachi Technoscience Co., Ltd. The optical film was cut to a width of 5 mm and a length of 15 mm to prepare a measurement sample, which was set in the device and heated once to 150°C at 5°C / min under a load of film thickness (μm) × 0.5g, cooled to 20°C, and further heated at 5°C / min. The CTE was calculated as the average value between 100 and 200°C from the TMA curve at the second heating.
[0142] <Measurement of weight average molecular weight> GPC measurements (1) Pretreatment method A DMF eluent (a 10 mmol / L lithium bromide-added solution) was added to the polyimide resins obtained in the Examples and Comparative Examples to a concentration of 2 mg / mL, and the mixture was heated at 80°C for 30 minutes with stirring. After cooling, the mixture was filtered through a 0.45 µm membrane filter to obtain a measurement solution. (2) Measurement conditions Column: 1 x TSKgel α-2500 ((7) 7.8 mm diameter × 300 mm) manufactured by Tosoh Corporation, 2 x α-M ((13) 7.8 mm diameter × 300 mm) Eluent: DMF (10 mmol / L lithium bromide solution) Flow rate: 1.0mL / min Detector: RI detector Column temperature: 40℃ Injection volume: 100μL Molecular weight standards: Standard polystyrene
[0143] <Optical film thickness> The thickness of the optical films obtained in the examples and comparative examples was measured using an ABS Digimatic Indicator (manufactured by Mitutoyo Corporation, "ID-C112BS").
[0144] <Example 1> [Preparation of polyimide resin (1)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 8.39 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TAHMBP were added to the flask so that they were 40.40 mol% and 60.61 mol% relative to TFMB, respectively, and stirred at room temperature for 16 hours. Then, 4-picoline was added at 60.61 mol% relative to TFMB, and acetic anhydride was added at 707.07 mol% relative to TFMB, and after stirring for 30 minutes, the internal temperature was gradually increased to 50 ° C. in 20 minutes, 60 ° C. in 20 minutes, and 70 ° C. in another 20 minutes, and stirred for another 3 hours to obtain a reaction solution. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a thread, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyimide resin (1). The weight average molecular weight was 409,000. [Production of Optical Film (1)] DMAc was added to the obtained polyimide resin (1) so that the concentration was 10 mass %, and polyimide varnish (1) was prepared. The obtained polyimide varnish (1) was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., product name "A4100") using an applicator so that the thickness of the free-standing film was 55 μm, and the free-standing film was dried at 50 ° C for 30 minutes and then at 140 ° C for 15 minutes to obtain a free-standing film. The free-standing film was fixed to a metal frame and further dried at 200 ° C for 60 minutes to obtain an optical film (1) having a thickness of 52 μm.
[0145] <Comparative Example 1> [Preparation of polyimide resin (2)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 7.81 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, TAHMBP was added to the flask so that the solid content was 101.01 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After that, 4-picoline was added at 60.61 mol% relative to TFMB, and acetic anhydride was added at 707.07 mol% relative to TFMB, and the mixture was stirred for 30 minutes. After that, the internal temperature was gradually increased to 50 ° C. in 20 minutes, 60 ° C. in 20 minutes, and 70 ° C. in another 20 minutes, and the mixture was stirred for another 3 hours to obtain a reaction solution. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a thread, and the precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyimide resin (2). The weight average molecular weight was 484,000. [Production of optical film (2)] DMAc was added to the obtained polyimide resin (2) so that the concentration was 10 mass %, and polyimide varnish (2) was prepared. The obtained polyimide varnish (2) was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., product name "A4100") using an applicator so that the thickness of the free-standing film was 55 μm, and the free-standing film was dried at 50 ° C for 30 minutes and then at 140 ° C for 15 minutes to obtain a free-standing film. The free-standing film was fixed to a metal frame and further dried at 200 ° C for 60 minutes to obtain an optical film (2) with a thickness of 50 μm.
[0146] <Comparative Example 2> [Preparation of polyimide resin (3)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 8.51 mass%, and 6FDAM was added so that the solid content was 11.11 mol% relative to TFMB, and TFMB and 6FDAM were dissolved in DMAc while stirring at room temperature. Next, 6FDA and an ester of trimellitic anhydride and 4,4'-biphenol were added to the flask so that the solid content was 40.40 mol% and 60.61 mol% relative to TFMB, respectively, and stirred at room temperature, but the viscosity increased over time and became a gel-like substance after 16 hours, making it difficult to dilute and dissolve, and the subsequent reaction procedures could not be carried out.
[0147] <Comparative Example 3> [Preparation of polyimide resin (4)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 7.65 mass%, and 6FDAM was further added so that the solid content was 42.86 mol% relative to TFMB, and TFMB and 6FDAM were dissolved in DMAc while stirring at room temperature. Next, 6FDA and an ester of trimellitic anhydride and 4,4'-biphenol were added to the flask so that the solid content was 40.40 mol% and 60.61 mol% relative to TFMB, respectively, and stirred at room temperature, but the viscosity increased over time, and after 16 hours it became a gel-like substance, making it difficult to dilute and dissolve, and subsequent reaction operations could not be carried out.
[0148] <Comparative Example 4> [Preparation of polyimide resin (5)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 9.43 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that the solid content was 101.01 mol% relative to TFMB, and the mixture was stirred at room temperature for 16 hours. After that, 4-picoline was added at 60.61 mol% relative to TFMB, and acetic anhydride was added at 707.07 mol% relative to TFMB, and the mixture was stirred for 30 minutes, after which the internal temperature was raised to 70°C and the mixture was stirred for another 3 hours to obtain a reaction solution. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a thread. The precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyimide resin (5). The weight average molecular weight was 255,000. [Production of optical film (5)] DMAc was added to the obtained polyimide resin (5) so that the concentration was 10 mass %, to prepare polyimide varnish (1). The obtained polyimide varnish (1) was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., product name "A4100") using an applicator so that the thickness of the free-standing film was 55 μm, and the free-standing film was dried at 50 ° C for 30 minutes and then at 140 ° C for 15 minutes to obtain a free-standing film. The free-standing film was fixed to a metal frame and further dried at 200 ° C for 60 minutes to obtain an optical film (5) having a thickness of 50 μm.
[0149] <Comparative Example 5> [Preparation of polyimide resin (6)] In a nitrogen atmosphere, TFMB and DMAc that had been thoroughly dehydrated to a water content of 700 ppm or less were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 10.56 mass%, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and BPDA were added to the flask so that the solid content was 40.40 mol% and 60.61 mol% relative to TFMB, respectively, and stirred at room temperature for 16 hours. Then, 4-picoline was added at 60.61 mol% relative to TFMB, and acetic anhydride was added at 707.07 mol% relative to TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70 °C and stirred for another 3 hours to obtain a reaction solution. The reaction solution obtained was cooled to room temperature and poured into a large amount of methanol in the form of a thread. The precipitate was taken out and immersed in methanol for 6 hours, and then washed with methanol. The precipitate was then dried under reduced pressure at 60°C to obtain polyimide resin (6). The weight average molecular weight was 172,000. [Production of optical film (6)] DMAc was added to the obtained polyimide resin (6) so that the concentration was 10 mass %, and polyimide varnish (6) was prepared. The obtained polyimide varnish (6) was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., product name "A4100") using an applicator so that the thickness of the free-standing film was 62 μm, and the free-standing film was dried at 50 ° C for 30 minutes and then at 140 ° C for 15 minutes to obtain a free-standing film. The free-standing film was fixed to a metal frame and further dried at 200 ° C for 60 minutes to obtain an optical film (6) with a thickness of 59 μm.
[0150] The optical films obtained in Example 1 and Comparative Examples 1, 4, and 5 were measured for breaking strain, thermal expansion coefficient, elastic modulus, total light transmittance, haze, and YI value, and the results are shown in Table 1. As for Comparative Examples 2 and 3, as described above, the polyimide resin could not be kept in a solution state during synthesis and could not be taken out, so that it was not possible to evaluate them as optical films. [Table 1]
[0151] As shown in Table 1, it was confirmed that the optical film formed from the polyimide resin of Example 1 had a high breaking strain and a low thermal expansion coefficient. In contrast, it was confirmed that the optical films formed from the polyimide resins of Comparative Examples 1 and 5 had a low breaking strain, and the optical film formed from the polyimide resin of Comparative Example 4 had a high thermal expansion coefficient. Therefore, it was found that the optical film formed from the polyimide resin of Example 1 was able to achieve both a high breaking strain and a low thermal expansion coefficient, and was also excellent in optical properties and elastic modulus.
Claims
1. Formula (1): 【Chemistry 1】 [In formula (1), X represents a divalent organic group, Y represents a tetravalent organic group, and * represents a bond.] The structural unit represented by X in formula (1) is represented by formula (4): 【change】 [In formula (4), A represents a single bond, R A1 and R A2 each independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 6 each independently represent a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom, s each independently represent an integer of 0 to 4, and * represents a bond] The structure includes Y in formula (1) is a group represented by formula (3): 【Chemistry 2】 [In formula (3), R 1 each independently represents a halogen atom, an alkyl group, an alkoxy group, an aryl group, or an aryloxy group which may have a halogen atom; R 2 ~R 5 each independently represents a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom; each m independently represents an integer of 0 to 3; n is 2 or 3; * represents a bond; 2 ~R 5 In at least one benzene ring having R 2 ~R 5 at least three of the groups are monovalent hydrocarbon groups which may have a halogen atom. and a structure represented by formula (5): 【Chemistry 3】 [In formula (5), B is a single bond, —O—, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, —SO 2 -, -S-, -CO-, -COO-, -PO-, -PO 2 -, -N(R B1 )-or-Si(R B2 ) 2 - represents R B1 and R B2 each independently represents a hydrogen atom or an alkyl group which may have a halogen atom; R 7 each independently represents a halogen atom, or an alkyl group, alkoxy group, aryl group, or aryloxy group which may have a halogen atom; each t independently represents an integer of 0 to 3; and * represents a bond. wherein, among the structural units represented by formula (1), a proportion of structural units in which Y is represented by formula (5) exceeds 30 mol %, and the polyimide resin has a weight average molecular weight of 160,000 or more.
2. 2. The polyimide resin according to claim 1, wherein X in formula (1) contains at least one of a divalent aromatic group, a divalent alicyclic group, and a divalent aliphatic group.
3. An optical film comprising the polyimide resin according to claim 1 .
4. The optical film according to claim 3 , wherein the total light transmittance is 85% or more.
5. 5. The optical film according to claim 3, having a yellowness index of 3.0 or less.
6. The optical film according to any one of claims 3 to 5, having an elastic modulus of 3.5 GPa or more.
7. The optical film according to any one of claims 3 to 6, which is a film for a front panel of a flexible display device.
8. A flexible display device comprising the optical film according to any one of claims 3 to 7.
9. The flexible display of claim 8 , further comprising a touch sensor.
10. The flexible display device according to claim 8 or 9, further comprising a polarizer.
Citation Information
Patent Citations
Method for producing film-forming material, film and liquid crystal display element
JP2013127049A
Polyimide film and method for producing the same
JP2020164771A
Polyimide and molded body thereof
WO2014046180A1
Polyimide resin, production method for polyimide resin, polyimide film, and production method for polyimide film
WO2020004236A1
Polyimide resin, varnish, and polyimide film
WO2020100904A1